Prevalence of major non-communicable diseases and their associated risk factors in Afghanistan: a systematic review and meta-analysis - Noormal, Ahmad Siyar; Winkler, Volker; Bhusari, Sneha Bansi; Horstick, Olaf; Louis, Valérie R.; Deckert, Andreas; Antia, Khatia; Wasko, Zahia; Rai, Pratima; Mocruha, Aline Frare; Dambach, Peter (Therapeutic advances in chronic disease, 2024)
Background: Non-communicable diseases (NCDs) are the leading cause of mortality worldwide, and increasingly so in low- and middle-income countries. Afghanistan is dealing with a double burden of diseases, yet there has been no evidence synthesis on the prevalence of major NCDs and their risk factors.Objective: This study aims to provide a comprehensive synthesis of the existing data on the prevalence of major NCDs and the common related risk factors in Afghanistan.Method: We systematically reviewed scientific articles from 2000 to 2022 that reported the prevalence of diabetes, chronic respiratory diseases (CRDs), cardiovascular diseases (CVDs) or cancer, and their risk factors in Afghanistan. Four online databases (PubMed, Web of Science, Cochrane and Google Scholar) and two local journals in Afghanistan (not indexed online) were systematically searched and screened. Two reviewers independently screened and appraised the quality of the articles. Data extraction and synthesis were performed using tabulated sheets.Results: Among 51 eligible articles, 10 (19.6%) focused on cancer, 10 (19.6%) on diabetes, 4 (7.8%) on CVDs, 4 (7.8%) on CRDs and 23 (45.1%) on risk factors as the primary outcome. Few articles addressed major NCD prevalence; no evidence of CVDs, cancer was 0.15%, asthma ranged between 0.3% and 17.3%, and diabetes was 12%. Pooled prevalence of hypertension and overweight were 31% and 35%, respectively. Central obesity was twice as prevalent in females (76% versus 40%). Similarly, gender differences were observed in smoking and snuff use with prevalence rates of 14% and 25% among males and 2% and 3% among females, respectively. A total of 14% of the population engaged in vigorous activity. Pooled prevalence for physical inactivity, general obesity, fruit and vegetable consumption, dyslipidaemia and alcohol consumption couldn't be calculated due to the heterogeneity of articles.Conclusion: Only little evidence is available on the prevalence of major NCDs in Afghanistan; however, the NCD risk factors are prevalent across the country. The quality of the available data, especially those of the local resources, is poor; therefore, further research should generate reliable evidence in order to inform policymakers on prioritizing interventions for controlling and managing NCDs.